2010
DOI: 10.1002/ppul.21229
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐9 polymorphism in infants with respiratory syncytial virus infection: An opposite effect in boys and girls

Abstract: The predominance of severe respiratory syncytial virus (RSV) bronchiolitis in boys compared to girls is well known, but its mechanism is not yet understood. This is the first study focusing on gender-specific genetic factors affecting the risk of severe RSV infection using a previously described cohort. We determined 347 single-nucleotide polymorphisms (SNPs) in 470 children hospitalized for RSV infection, their parents, and 1,008 random population controls. We tested if these SNPs exerted a different effect i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 25 publications
1
49
0
1
Order By: Relevance
“…To assess whether IL-9 may contribute to allergy in CF patients, we determined the effect of the non-synonymous IL9 p.Thr117Met (c.350C>T, rs2069885) polymorphism, known to be associated with lung function and sensitization3637 on total and Aspergillus -specific IgE levels in CF patients (Supplementary Table 1). Previous association studies demonstrated the existence of sex dimorphism linked to this polymorphism3637.…”
Section: Resultsmentioning
confidence: 99%
“…To assess whether IL-9 may contribute to allergy in CF patients, we determined the effect of the non-synonymous IL9 p.Thr117Met (c.350C>T, rs2069885) polymorphism, known to be associated with lung function and sensitization3637 on total and Aspergillus -specific IgE levels in CF patients (Supplementary Table 1). Previous association studies demonstrated the existence of sex dimorphism linked to this polymorphism3637.…”
Section: Resultsmentioning
confidence: 99%
“…Genes controlling infections that appear to be sex dependent have been observed also with other infectious agents such as viruses [69–71], bacteria [72], parasites [58], and fungi [73] and helminths [74]. Some of sex-dependent QTLs exhibit a higher or exclusive influence on susceptibility in females [58, 69, 7173] or males [69, 7174], phenotypic effect of other genes is present in both sexes, but with opposite direction of effect [69, 70]. All these reported loci are situated on autosomal chromosomes.…”
Section: Discussionmentioning
confidence: 99%
“…One of these studies showed a sex-specific protective effect for wheeze in girls with a particular haplotype in the IL-9 receptor gene (28) , and another identified associations (in male subjects only) between the IL-9 polymorphisms rs2069885 and rs2069882 and phenotypes for lung function and multiple-allergen sensitization, respectively (29) . Lastly, a study in infants showed effect modification by sex for the association between the IL-9 polymorphism rs2069885 and susceptibility to severe RSV bronchiolitis, where the variant appeared protective in girls, but was linked with increased risk in boys (30) . In the present study, tests for the interaction between sex and the IL-9 polymorphism rs2069885 in the CAMP cohort were not significant for lung function phenotypes (percent predicted FEV1, airway hyper-responsiveness) or for the severe asthma exacerbation outcome (p>0.5 for interaction terms).…”
Section: Discussionmentioning
confidence: 99%